An Update on Treatments and Interventions for Male Infertility, and the Role of Nutriceutical Food Supplementation - Comhaire, Frank H.; Mahmoud, Ahmed (Journal of Pharmacy and Nutrition Sciences, 2012)
Congenital factors have been thoroughly explored in recent years revealing the role of genetic mutations and polymorphisms, and highlighting the contribution of epigenetics in the pathogenesis of certain forms of infertility. Acquired male infertility is commonly due to varicocele, male accessory gland infection, immunological infertility, and idiopathic oligozoospermia. The mechanisms by which these causes interfere with male reproduction are endocrine deregulation, inflammation through prostaglandins and cytokines, and oxidative overload damaging the cell membrane, inducing mutagenesis of the DNA, and impairing mitochondrial energy production. Causal treatment includes (non-surgical) interruption of spermatic venous reflux in varicocele, adequate antibiotic treatment with third generation Quinolones in accessory gland infection, assisted reproduction techniques in immunological infertility, and the anti-estrogen Tamoxifen for idiopathic oligozoospermia. In addition, a novel nutriceutical food supplement (NFS) has been formulated that aims at correcting the pathological mechanisms and at reducing the influence of detrimental environmental factors. Complementary NFS-treatment also may improve the fertilizing capacity of spermatozoa in some patients with a congenital cause of sperm deficiency. The efficiency of adding this NFS to causal therapy, or in assisted reproduction is expressed as numbers of couples needed to treat (NNT) to obtain one additional pregnancy.